Marsh restoration in front of seawalls is an economically justified nature-based solution for coastal protection - Ernie I. H. Lee; Heidi Nepf (Communications Earth & Environment)
Abstract A marsh-fronted seawall is a hybrid nature-based coastal protection solution because it attenuates wave energy, reduces erosion, and provides ecosystem services. However, we still have a limited understanding of how to quantify the marsh wave attenuation benefits for economic analysis. Here, we incorporate a prediction of wave attenuation that accounts for species-specific morphology and structural stiffness into a 1-D wave model and validate it with field measurements. Our results show that the wave attenuation varies by a factor of two across different vegetation species. Further, we performed a benefit-cost analysis, in which the economic benefits represent the environmental services value and avoided seawall heightening cost that would otherwise be required to deliver the same overtopping rate without vegetation. We applied the model to a real-world, marsh-fronted seawall design at Juniper Cove, Massachusetts. Although the benefit of marsh-fronted seawalls is sensitive to discount rate, they have benefit-cost ratios greater than one, indicating that it is an economically justified nature-based solution. Further, we found that wave attenuation and benefit-cost ratio are more sensitive to water depth than wave height. Our study demonstrates the importance of considering the coastal protection of marshes and economic benefits in one framework.